THE IMPLEMENTATION OF TASK-BASED LANGUAGE TEACHING (TBLT) IN TEACHING WRITING: CLASSROOM ACTION RESEARCH AT ONE OF JUNIOR HIGH SCHOOLS IN BANDUNG - Mutiara Stepani, - (2011)
Writing is one of the skills taught in English as a Foreign Language (EFL) classroom. There is no doubt that the students from elementary to senior high school learn how to write texts well, since the demand of writing mastery revealed in the government curriculum. This study investigates the implementation of Task-Based Language Teaching (TBLT) in teaching writing. The aims of this study were to find out the improvement of students' quality after implementing TBLT in teaching writing and to reveal students' responses toward the implementation of TBLT in teaching writing. This study is a classroom action research which was conducted at one of the junior high schools in Bandung and participated by 19 eighth-grade students. For the analysis, it uses qualitative approach supported with quantitative data to answer the research questions. Observation, students writing tests, questionnaires, and interview were employed to gain the data. This study shows that the implementation of TBLT in teaching learning process was quite successful, despite some limitations of this study. The data gained from students' writing tests show that TBLT can help students improve their writing quality. The mean of the students' writing scores in cycle 3 was 68.6 with seventeen students (89.5%) achieved scores above KKM. In addition, most of the students respond positively towards the use of TBLT during the teaching learning process. The data from observation show that the students actively accomplished their tasks. The data from questionnaires also reveal that TBLT can help the students work cooperatively in group and motivate their learning process. Thus, data from interview reveal that the students enjoyed, were interested and motivated to learn writing through TBLT. Based on the findings, it is recommended for further studies that TBLT can be implemented in teaching writing at any skills and any school levels. Therefore, it is important to select the writing material which is relevant to students' needs and interests.